1987
DOI: 10.1159/000124714
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Changes in the Mechanisms Controlling Prolactin Secretion and Phosphatidylinositol Turnover in Male Rats: Effect of Phosphatidylserine

Abstract: The present study was undertaken in order to better characterize the functional state of anterior pituitary gland in young and old rats by using prolactin secretion and incorporation of radioactive phosphate into phosphatidylinositol (PI) as markers. The in vitro incorporation of radiolabeled phosphate into anterior pituitary PI was significantly (p< 0.01) greater in young (3–5 months) than in aged (24–25 months) male Sprague-Dawley rats. No significant difference was found in the incorporation by pituitary ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
(18 reference statements)
1
6
1
Order By: Relevance
“…Consequently, all PRL measurements greatly increased in our old female rats. This finding corresponds to the higher PRL content previously reported (Cocchi et al, 1986;Bonetti et al, 1987).…”
Section: Discussionsupporting
confidence: 91%
“…Consequently, all PRL measurements greatly increased in our old female rats. This finding corresponds to the higher PRL content previously reported (Cocchi et al, 1986;Bonetti et al, 1987).…”
Section: Discussionsupporting
confidence: 91%
“…A reduction of prolactin secretion in rat lactotrophs during aging was also obtained after chronic treatment with PS (Toffano & Bruni, 1980;Zauli et al, 1984;Toffano, 1985). The changes in lactotrophs membrane fluidity during aging has been shown to affect phosphatidylinositol (PI) metabolism; PS was found to reduce in vitro 32P incorporation into PI and such an effect was associated with the inhibition of prolactin secretion (Bonetti et al, 1987).…”
Section: Discussionmentioning
confidence: 95%
“…In previous studies, administration of 200-300 mg/day of PS containing omega-3 fatty acids was found to have beneficial effects, purely symptomatic or neuroprotective [9,15,16,17,18,19]ones, on various types of cognitive impairment, ranging from age-associated cognitive decline to Alzheimer's disease [7,8,20,21,22,23,24]. …”
Section: Discussionmentioning
confidence: 99%